Oracle autonomous database in enterprise architecture : a practical approach to understanding Oracle Cloud infrastructure autonomous databases for better consolidation, automation, and security /: a practical approach to understanding Oracle Cloud infrastructure autonomous databases for better consolidation, automation, and security. (2022) - Sharma, Bal Mukund; Mohanram, Krishnakumar; Panda, Rashmi
No abstract available